Biblioteki naukowe i instytucje kultury jako miejsca kwerend genealogicznych. Poradnik w świadczeniu usług informacyjnych na temat materiałów do badań nad genealogią = Scientific libraries and cultural institutions as a places for genealogical searches. A guide to scientific information services on genealogy research material - Naplocha, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Genealogy research is becoming an increasingly popular hobby and a way to answer the question "where do we come from". In times of increased availability of digital sources, an increasing number of amateur family genealogists have the opportunity to search for their ancestors. Due to the fact that people doing genealogical searches are also becoming more and more frequent guests of scientific libraries, this article is a response to this phenomenon in terms of providing information services by librarians.
Keywords: genealogia; biblioteki naukowe; instytucje kultury; genealogiczne bazy danych; informacja naukowa; genealogy; scientific library; cultural institutions; genealogical databases; scientific information